Being Participatory with Videography - Neufeld, Michael Todd; Ripley, Paul (Springer, 2024)
Social media platforms such as Facebook, YouTube, Instagram, and TikTok are powerful distribution networks for stories and ideas and an integral aspect of many (if not most) young people’s lives. Participatory video (PV) methods offer a collaborative framework for working with young people to help them express their interests and perspectives within digital storytelling spaces. Reaching young people in ways that many traditional research methods cannot, PV helps young people analyse their experiences and communicate their ideas and insights on things that affect them. By promoting the collective identification of important patterns within their stories, PV can elicit nuanced narratives and promote shared understandings through digital media. These shared understandings develop not only between adults and young people, but also between participants and other young people alike. The ability for PV to convey deeper truths and understanding makes it a powerful tool for change. Using “The Creating Space Project: Youth Voice in Healthcare” as an exemplar, this chapter explores the advantages and challenges of undertaking PV projects with young people. The authors offer specific techniques, resources, and advice that facilitate collaboration with young people to identify the health issues most important to them. The videos produced through PV can be used to amplify the participants’ ideas about what should be done to resolve the issues they have identified.
Keywords: Child and Youth Health; Participatory Video; Participatory Drama; Participatory video (PV); Digital storytelling; Participatory action research (PAR); Youth voice; Youth health